1999
DOI: 10.1159/000029097
|View full text |Cite
|
Sign up to set email alerts
|

Demonic Attributions in Nondelusional Disorders

Abstract: Objective: Belief in demonic influence has repeatedly been described as a delusion in schizophrenic patients. The goal of this explorative study was to examine the frequency, as well as the psychodynamic and social functions of such beliefs in a sample of nondelusional patients. Method: The sample consisted of 343 psychiatric outpatients who described themselves as religious. In semistructured interviews they were asked to give their view of demonic causality of their illness. Results: A high prevalence of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…The patient believed that half of her symptoms were due to the mental disorder and the other half to something unknown but sensed by her to have a spiritual root. In addition, different experts in the field of exorcism considered that the symptoms of this psychotic patient may be due to a malign presence 27. Following exorcisms, the patient believed some symptoms, particularly mood, had improved.…”
Section: Discussionmentioning
confidence: 98%
“…The patient believed that half of her symptoms were due to the mental disorder and the other half to something unknown but sensed by her to have a spiritual root. In addition, different experts in the field of exorcism considered that the symptoms of this psychotic patient may be due to a malign presence 27. Following exorcisms, the patient believed some symptoms, particularly mood, had improved.…”
Section: Discussionmentioning
confidence: 98%
“…A high prevalence of such beliefs was not only found in schizophrenia (56%) but also in non-delusional patients: affective disorders (29%), anxiety disorders (48%), personality disorders (37%) and adjustment disorders (23%). The authors concluded that demonic influence should be interpreted against the cultural and religious background which is shaping causal models of mental distress in the individual [21]. Occasionally, rigidly held nondelusional beliefs can become amplified and overvalued by an individual or group leading to extreme behavior in its service.…”
Section: Extreme Overvalued Belief: Possible Etiologiesmentioning
confidence: 99%
“…For example, studies have found that the traditional possession model of mental illness is now giving way to more modernized idioms of psychological "tension" and "depression" in Kerala (Halliburton, 2005). Outside of India, some have attempted to correlate the phenomenology of possession with psychiatric models of dissociative states (Ferracuti, Sacco, & Lazzari, 1996), while others have studied descriptively the frequency of possession attributions across both psychotic and non-psychotic diagnostic categories (Pfeifer, 1999). Progressive thinkers have even recommended that mental health professionals work with rather than against beliefs about possession and exorcism (such as allowing patients to engage in combined treatment), so as to improve compliance and outcomes (Vlachos et al, 1997).…”
Section: Integral Yoga Psychology: Clinical Correlationsmentioning
confidence: 99%